A mixed methods feasibility study to evaluate the use of a low-intensity, nurse-delivered cognitive behavioural therapy for the treatment of irritable bowel syndrome. Issue 6 (17th June 2014) - Dainty, Andrew David; Fox, Mark; Lewis, Nina; Hunt, Melissa; Holtham, Elizabeth; Timmons, Stephen; Kinsella, Philip; Wragg, Andrew; Callaghan, Patrick
Abstract : Introduction: Irritable bowel syndrome (IBS) is characterised by symptoms such as abdominal pain, constipation, diarrhoea and bloating. These symptoms impact on health-related quality of life, result in excess service utilisation and are a significant burden to healthcare systems. Certain mechanisms which underpin IBS can be explained by a biopsychosocial model which is amenable to psychological treatment using techniques such as cognitive behavioural therapy (CBT). While current evidence supports CBT interventions for this group of patients, access to these treatments within the UK healthcare system remains problematic. Methods and analysis: A mixed methods feasibility randomised controlled trial will be used to assess the feasibility of a low-intensity, nurse-delivered guided self-help intervention within secondary care gastrointestinal clinics. A total of 60 participants will be allocated across four treatment conditions consisting of: high-intensity CBT delivered by a fully qualified cognitive behavioural therapist, low-intensity guided self-help delivered by a registered nurse, self-help only without therapist support and a treatment as usual control condition. Participants from each of the intervention arms of the study will be interviewed in order to identify potential barriers and facilitators to the implementation of CBT interventions within clinical practice settings. Quantitative data will be analysed using descriptive statistics only. Qualitative data will be analysed using a group thematic analysis. Ethics and dissemination: This study will provide essential information regarding the feasibility of nurse-delivered CBT interventions within secondary care gastrointestinal clinics. The data gathered during this study would also provide useful information when planning a substantive trial and will assist funding bodies when considering investment in substantive trial funding. A favourable opinion for this research was granted by the Nottingham 2 Research Ethics Committee. Trial registration number: ISRCTN: 83683687 (http://www.controlled-trials.com/ISRCTN83683687 ).